Factors influencing food choice of athletes at international competition events. (1st February 2018) - Pelly, Fiona E.; Burkhart, Sarah J.; Dunn, Peter
Abstract: Although the nutrient requirements and dietary intake of athletes have been thoroughly investigated, little is known about the influences on their food choice, particularly prior to and during competition. This study sought to investigate factors that influence food selection of athletes at two similar international competition events: the Melbourne 2006 and Delhi 2010 Commonwealth Games. A secondary aim was to explore differences in these factors between at each event given the culturally diverse locations. A survey developed for this study was distributed to athletes in the village dining hall at both events. Athletes scored a selection of factors influencing food choice on a scale of 1 (not important) to 5 (very important). A total of 769 individuals completed the questionnaire in total, with 351 (46%) from Delhi and 418 (54%) from Melbourne. Overall, athletes rated nutrient composition (M = 4.22), stage of competition (M = 4.09), time of day (M = 4.02) and familiarity of the food (M = 4.07) higher than sensory properties (smell M = 3.88; visual appearance M = 3.22) when making a food selection. Visual appearance ( p  = 0.01), stage of competition ( p  < 0.001) and time of day ( p  = 0.01) had greater influence in Delhi than Melbourne. Overall, a significantly higher proportion of female athletes rated smell ( p  < 0.001) and familiar food ( p  < 0.001) as important compared to males. The stage of competition and nutrition composition was rated as very important by the greatest proportion of athletes from weight category sports (61.9%) and endurance sports (57.9%) respectively. The influence of the coach and team mates was less of an influence than other factors, but more so for athletes from Non-Western regions. Further investigation of the various determinants and motives for food section of athletes from a range of sports and cultures is warranted.